Reorganization of Cities with Hot Climates - B, Kodirova Sh.; B, Xujayorova O.; Q., Ruziboyeva D. (International Journal on Integrated Education, 2023)
The purpose of this article is to evaluate the landscape design of urban gardens and parks with a hot climate, as a means of aesthetic and ecological adaptation of the cultural space of the city with a hot climate. The parks of culture and recreation are the most popular because they are within walking distance. These areas play a major ecological and aesthetic role in the development of the city, however, a significant problem is the deterioration of their landscape condition.